No independent association between dietary calcium/vitamin D and appendicular lean mass index in middle-aged women: NHANES cross-sectional analysis (2011–2018) - Zhengwei Lai; Fang Jin; Chunmei Zhu; Zhongxin Zhu (Scientific Reports)
Abstract Skeletal muscle preservation during midlife is critical for preventing sarcopenia in aging populations. While calcium and vitamin D are recognized for their musculoskeletal benefits, their specific associations with muscle mass in middle-aged women remain unclear. This cross-sectional study analyzed data from 2,496 women aged 40–59 years in the NHANES (2011–2018). Multivariable linear regression models adjusted for demographics, lifestyle factors, and comorbidities evaluated associations between dietary calcium, vitamin D intakes and appendicular lean mass index (ALMI), with subgroup analyses by menopausal status and other covariates. After full adjustment, neither dietary calcium nor vitamin D intake showed significant associations with ALMI. Null findings persisted across all subgroups. Dietary calcium and vitamin D intake were not independently associated with ALMI in middle-aged women. These results highlight the need to investigate broader nutritional patterns or synergistic mechanisms influencing muscle health during midlife.